Chemical and antibacterial data of synthesized thioureido derivatives - Abdul Kadir, Maisara; Ramli, Rafidah N.Hikma; Mohd Yusof, Mohd Sukri; Ismail, Noraznawati; Ngah, Nurziana; Haris, Noorazilah S.H. (Elsevier, 2019)
This paper provided comprehensive data on spectroscopic and antibacterial activities of thioureido compounds which are rele- vant with research article entitled “Synthesis, Spectroscopic Studies and Antibacterial Activity of New Lauroyl Thiourea Amino Acid Derivatives” [1]. Based on the reported study, four new thi- oureido derivatives, namely 3-(3-dodecanoyl-thioureido)propionic acid (R1), 2-(3-dodecanoyl-thioureido)-3-methyl butyric acid (R2), (3-dodecanoyl-thioureido)acetic acid (R3) and 2-(3-dodecanoyl- thioureido)-3-phenyl propionic acid (R4) were characterized by elemental analysis, Fourier Transform Infrared (FTIR), 1H Nuclear Magnetic Resonance (1H NMR) and 13C Nuclear Magnetic Resonance (13C NMR), and Ultraviolet Visible spectroscopy (UV-Vis). The preliminary results from antibacterial assay which were tested against Gram-positive bacteria such as Bacillus subtilis, Staphylococcus epidermidis, Staphylococcus aureus and Gram-negative bacteria such as Escherichia coli, Salmonella typhimurium are also described.